Approach to Hyponatremia in Congestive Heart Failure: A Survey of Canadian Specialist Physicians and Trainees. Issue 1 (20th January 2016) - Miller, Amanda; Kuehl, Bonnie; Tennankore, Karthik; Soroka, Steven
Background: Hyponatremia is a recognized complication of congestive heart failure (CHF) and is associated with reduced survival. Therefore, early identification and appropriate management of hyponatremia is important. The aim of this study was to determine the general approach amongst Canadian healthcare practitioners and trainees to the identification and management of hyponatremia complicating CHF. Methods: Respondents completed 15 multiple-choice style questions in 3 case scenarios regarding the approach to management of hyponatremia complicating CHF using an online survey onUKidney.com between November 2012 and May 2013. Results were presented as a proportion of averaged correct/incorrect responses amongst Canadian nephrologists, cardiologists, internists and trainees in each of two domains; pathophysiology and management. Management was further subdivided into correct and incorrect use of diuretic therapy, hypertonic saline, oral urea tablets, vasopressin receptor antagonists (vaptans) and rate of sodium correction. Correct responses were determined by an expert panel of Canadian nephrologists and cardiologists based on review of evidence informed guidelines and current recommendations. Results: There were 1757 responses to our online survey amongst 455 Canadian respondents, 1139 of which were from cardiologists, nephrologists, general internists, or trainees. Overall, the pathophysiology governing hyponatremia in CHF was correctly identified 68.7 % of the time ( n = 380 responses, averaged over 4 questions). Hyponatremia was managed inappropriately 43.6 % of the time, with trainees scoring best overall with correct responses 60.3 % of the time ( n = 759 responses, over 11 questions). Importantly, an incorrect rate for sodium correction was selected 61.1 % of the time overall, ( n = 211 responses, averaged over 3 questions). Conclusions: This study identified that there are differences in the understanding of pathophysiology and management strategies for hyponatremia in the context of CHF amongst Canadian specialist physicians and trainees. A more consistent approach to hyponatremia is required and might best be achieved through formal knowledge translation.